Metal-free polypeptide redox flow batteries. Issue 16 (21st July 2022) - Liang, Zhiming; Nguyen, Tan P.; Attanayake, N. Harsha; Easley, Alexandra D.; Lutkenhaus, Jodie L.; Wooley, Karen L.; Odom, Susan A.
Abstract : Metal-free redox flow batteries with TEMPO-based polypeptide catholytes and viologen-based polypeptide anolytes were demonstrated. Post-cycling analysis indicated the main source of capacity fade was degradation of the redox-active pendant groups. Abstract : Non-aqueous organic redox flow batteries (NAORFBs) are considered emerging large-scale energy storage systems due to their larger voltage window as compared to aqueous systems and their metal-free nature. However, low solubility, sustainability, and crossover of redox materials remain major challenges for the development of NAORFBs. Here, we report the use of redox active α-helical polypeptides suitable for NAORFBs. The polypeptides exhibit less crossover than small molecule analogs for both Daramic 175 separator and FAPQ 375 PP membrane, with FAPQ 375 PP preventing crossover most effectivley. Polypeptide NAORFBs assembled with a TEMPO-based polypeptide catholyte and viologen-based polypeptide anolyte exhibit low capacity fade ( ca. 0.1% per cycle over 500 cycles) and high coulombic efficiency (>99.5%). The polypeptide NAORFBs exhibit an output voltage of 1.1 V with a maximum capacity of 0.53 A h L −1 (39% of the theoretical capacity). After 500 charge–discharge cycles, 60% of the initial capacity was retained. Post cycling analysis using spectral and electrochemical methods demonstrate that the polypeptide backbone and the ester side chain linkages are stable during electrochemical cycling. Taken together, these polypeptides offer naturally-derived, deconstructable platforms for addressing the needs of metal-free energy storage.